2019
DOI: 10.1111/eva.12807
|View full text |Cite
|
Sign up to set email alerts
|

Artificial selection causes significant linkage disequilibrium among multiple unlinked genes in Australian wheat

Abstract: Australia has one of the oldest modern wheat breeding programs worldwide although the crop was first introduced to the country in 1788. Breeders selected wheat with high adaptation to different Australian climates, while ensuring satisfactory yield and quality. This artificial selection left distinct genomic signatures that can be used to retrospectively understand breeding targets, and to detect economically important alleles. To study the effect of artificial selection on modern cultivars and cultivars relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
3
16
0
1
Order By: Relevance
“…Since breeders select directly for earliness, a single trait that is affected by both Vrn and Ppd genes, it is likely that alleles shortening cycle length at both loci were selected simultaneously in breeding programs. This has been shown to be the case in recent studies conducted with Australian bread wheat (Joukhadar et al, 2019) and Italian durum wheat (Taranto et al, 2020) which have demonstrated that artificial selection involved strong simultaneous selection on specific alleles for vernalization and photoperiod genes.…”
Section: Effects Of the Vrn-1 And Ppd-1 Alleles And Allele Combinatiomentioning
confidence: 80%
“…Since breeders select directly for earliness, a single trait that is affected by both Vrn and Ppd genes, it is likely that alleles shortening cycle length at both loci were selected simultaneously in breeding programs. This has been shown to be the case in recent studies conducted with Australian bread wheat (Joukhadar et al, 2019) and Italian durum wheat (Taranto et al, 2020) which have demonstrated that artificial selection involved strong simultaneous selection on specific alleles for vernalization and photoperiod genes.…”
Section: Effects Of the Vrn-1 And Ppd-1 Alleles And Allele Combinatiomentioning
confidence: 80%
“…The selective pressure on these genes/QTLs marked the transition from LR, through OC, to MC. In particular, the locus Glu-1 was reported to be nearly fixed in modern bread (Joukhadar et al, 2019) and the durum wheat germplasm (Maccaferri et al, 2019).…”
Section: Outlier Loci and Selection Signaturesmentioning
confidence: 99%
“…Therefore, QTLs for plant height (PH) were also included ( Table S1 ). Using a large Australian wheat population, Joukhadar et al [ 23 ] showed that long-term artificial selection left distinct genomic signatures that can be used to retrospectively understand breeding targets, and to identify economically important alleles, such as the regions including Glu-B1 , TaGw2-6A , Cre8 , Ppd-D1 , Rht-B1 , Vrn-B1 , TaSus1-7A , TaSAP1-7A and Psy-A1 plus multiple QTLs affecting wheat yield and yield components. The recently assembled genome of the Italian durum wheat cv .…”
Section: Genetics Of Grain Yield In Wheatmentioning
confidence: 99%
“…Different breeding approaches including quantitative trait loci (QTL) and genome-wide association studies (GWAS) are being applied to increase the grain yield potential of durum wheat through molecular marker-assisted selection (MAS). In fact, multiple QTLs with large and small effects have been mapped on all wheat chromosomes and they have been recently published [ 20 , 21 , 22 , 23 , 24 ]. Therefore, due to the importance of this complex trait and to summarize the available information on the genetics of grain yield in durum wheat, the objective of this review is to analyze in a comprehensive manner the most recent findings associated with the genetics, genomics and the identification of QTL for grain yield-related traits in durum wheat.…”
Section: Introductionmentioning
confidence: 99%